2014
DOI: 10.1111/resp.12335
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial ultrasound‐guided transbronchial needle biopsy for the diagnosis of intrathoracic lymph node metastases from extrathoracic malignancies: A meta‐analysis and systematic review

Abstract: Intrathoracic lymph node metastases in patients with extrathoracic malignancies are a common clinical manifestation. Several studies evaluating intrathoracic lymph node metastases in patients with extrathoracic malignancy by using the endobronchial ultrasoundguided transbronchial needle aspiration (EBUS-TBNA) have been reported. The objective of this meta-analysis is to investigate the diagnostic value of EBUS-TBNA for diagnosing intrathoracic lymph node metastases in patients with extrathoracic malignancies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 37 publications
0
24
0
1
Order By: Relevance
“…Die können mittels EBUS-TBNA diagnostiziert werden; die gepoolte Sensitivität liegt bei 85 %, die Spezifität bei 99 % [39].…”
Section: Der Pneumologeunclassified
“…Die können mittels EBUS-TBNA diagnostiziert werden; die gepoolte Sensitivität liegt bei 85 %, die Spezifität bei 99 % [39].…”
Section: Der Pneumologeunclassified
“…A meta‐analysis including six studies of 533 patients showed that EBUS TBNA conferred high diagnostic accuracy for intrathoracic lymph node metastases in patients with extrathoracic malignancies (pooled sensitivity 85% and specificity 99%) …”
Section: Bronchoscopic Intervention and Imagingmentioning
confidence: 99%
“…Endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA), a minimally invasive daycare procedure, is currently the preferred method for sampling mediastinal lymph nodes. It is the method of choice for the staging of lung cancer, and is a useful modality in the assessment of other mediastinal disorders including sarcoidosis, tuberculosis or metastases from extrathoracic malignancies . Owing to these advantages, there is not only an urgent need but also a great demand for respiratory physicians and thoracic surgeons to be trained in this technique.…”
Section: Introductionmentioning
confidence: 99%